Implementasi Pertanggungjawaban Pelaku Tindak Pidana Mengangkut, Menguasai, Atau Memiliki Hasil Hutan Kayu Yang Tidak Dilengkapi Secara Bersama Surat Keterangansahnya Hasil Hutan (Studi Putusan Nomor: 259/Pid.Sus/LH/2019/PN Kot) - Candra Agung Laksana; Bambang Hartono; Zainudin Hasan (Universitas Batanghari Jambi, 2021)
Criminal demonstrations that happen in the public arena are criminal demonstrations against property (material wrongdoings), like robbery, blackmail, theft, extortion, defacement and confinement. The new criminal demonstration is the criminal demonstration of moving, controlling, or having wood woodland items that are not joined by an authentication of lawfulness of timberland items. The examination technique utilized standardizing and exact juridical methodologies. The kind of information utilized is auxiliary information and essential information. Gathering information through library exploration and field research. The information examination utilized was subjective juridical. The elements making the culprit perpetrate the criminal demonstration of shipping, controlling, or having lumber woods items that are not joined by an endorsement of lawful woodland items dependent on Decision Number: 259/Pid.Sus/LH/2019/PN Kot are financial and instructive components, the trouble in getting a grant and absence of oversight. The execution of responsibility for the culprit of a criminal demonstration of shipping, controlling, or possessing wood woodland items which isn't joined by an endorsement of lawful backwoods items dependent on Decision Number: 259/Pid.Sus/LH/2019/PN Kot is deserving of detainment for 1 (one) 1 (one) month and a fine of Rp. 500,000,000.00 (500,000,000 rupiah) gave that assuming the fine isn't paid, it is supplanted by detainment of 1 (one) month.